The expression that correctly shows the sum of opposite numbers is:
\[ (-25) + 25 = 0 \]
This is because opposite numbers, such as -25 and 25, always sum to zero.
Responses
(−25)+(−25)=−50
left parenthesis negative 25 right parenthesis plus left parenthesis negative 25 right parenthesis equals negative 50
(−25)+25=50
left parenthesis negative 25 right parenthesis plus 25 equals 50
(−25)+(−25)=0
left parenthesis negative 25 right parenthesis plus left parenthesis negative 25 right parenthesis equals 0
(−25)+25=0
1 answer
The expression that correctly shows the sum of opposite numbers is:
\[ (-25) + 25 = 0 \]
This is because opposite numbers, such as -25 and 25, always sum to zero.